Catering Management / Third Edition - Scanlon Nancy Loman (John Wiley And Sons, Inc, 2007)
This book offers detailed advice on all the crucial business aspects of the subject for on- and off- premise catering. Preface, Acknowledgements, Historical Banqueting, Styles of Catering Operations, Catering Foodservice Development, Catering Sales and Marketing and Computer-Software Support, Catering Menu Program, Food-and-Beverage Operational Controls, Catering Menu Pricing and Controls, Catering Menu Design, Catering Beverage Management, Quality-Service and Standards Training, Managing Catering Equipment, Bibliography, Index.